Cholón and the linguistic prehistory of Northern Peru: triangulating toponymy, substrate lexis, and areal typology - Matthias Urban (Linguistic Discovery, 2021)
At the eve of Spanish conquest, Northern Peru is thought to have been home to a multitude of languages of relatively modest geographical extension, especially when compared with the widespread Quechuan and Aymaran languages. In this contribution, I suggest the possibility that a language or several languages relatively closely related to Cholón were spoken in a much wider part of Northern Peru than that in which Cholón is historically attested. A prior “Cholonoid” area might have covered not only the western part of today’s San Martín department, but also almost the entire department of Cajamarca as well as parts of La Libertad and Amazonas. This interpretation results from a triangulation of three independent lines of evidence, namely the toponymic record, substrate lexis in the local variety of Quechua at Chachapoyas, and typological properties of the extinct northern Peruvian languages.